The State of the Sub-discipline: Mapping Parliamentary and Legislative Studies Using a Survey and Bibliometric Analysis of Three of Its Journals. Issue 4 (29th April 2022) - Bhattacharya, Caroline; Hart, Gavin; Haughey, Sean; Holden Bates, Stephen; Meakin, Alexandra
Abstract: We map the current state of parliamentary and legislative studies through a survey of 218 scholars and a bibliometric analysis of 25 years of publications in three prominent sub-field journals. We identify two groupings of researchers, a quantitative methods, rational choice-favouring grouping and a qualitative methods, interpretivism-favouring grouping with a UK focus. Upon closer examination, these groupings share similar views about the challenges and future of the sub-discipline. While the sub-discipline is becoming more diverse and international, US-focused literature remains dominant and distinct from UK-focused literature, although there are emerging sub-literatures which are well placed to link them together.